2021
DOI: 10.5114/kitp.2021.109562
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the effect of surgical treatment in secondary proliferative disease with lung involvement

Abstract: Introduction: Surgical treatment of neoplastic lung metastases is a big therapeutic problem, at the stage of qualifying for the procedure, in the surgical technique itself, and in the tactics of managing subsequent disease relapses. The most doubtful aspect is determining which factors influence the prolongation of survival in patients with such a diagnosis. Aim: To determine which factors influence the effectiveness of surgical treatment of neoplastic metastases to the lungs. Material and methods: A group of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In our research, the rate was around 7%, of which around 30% were not related to the surgery. The risk of perioperative death in the study group was 0.5% [ 3 , 4 ]. For the purposes of the present study, the PFS time was defined as the appearance of new lung lesions after metastasectomy or the date of death or the date of completion of the observation assuming that the patient was alive up to that date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our research, the rate was around 7%, of which around 30% were not related to the surgery. The risk of perioperative death in the study group was 0.5% [ 3 , 4 ]. For the purposes of the present study, the PFS time was defined as the appearance of new lung lesions after metastasectomy or the date of death or the date of completion of the observation assuming that the patient was alive up to that date.…”
Section: Discussionmentioning
confidence: 99%
“…Here, too, often erroneous results of publications dealing with this problem are produced. In our previous studies, after creating two comparable groups of patients, we found longer survival in patients without relapse after metastasectomy (median survival 71 months without relapse versus 36 months with relapse) [ 3 , 4 ]. Subsequent metastasectomies are directly related to disease progression.…”
Section: Introductionmentioning
confidence: 99%